Managing people and organizations : Peter Drucker's legacy - Stein, Guido, 1963- (Emerald, 2010)
Drucker was timely and inopportune at the same time. It is clear that from his extensive, solid and continual formation there has been born a singular, and at the same time multi-faceted, philosophy, which is deliberately difficult to summarize. Drucker was one of the first, if not the first, to discover the imminence of this far-reaching change. Precisely because he is not a specialist, he was able to perceive details and nuances that had been missed by the great gurus of management. This is why Drucker is considered to be the forerunner of modern management, as well as other concepts. This book shows the lesser-known side of Peter Drucker as far as his views on his own ideas are concerned. Drucker is most commonly thought of as a management theoretician; undoubtedly this is the most well known dimension of his work. What could be considered new and useful is that Drucker's aim was to write about man in his (man's own) social context. Drucker poured and concentrated his knowledge on man and organizations, drawing from what he learned from his European background and after expanded and practically texted in his American years.
Keywords: Drucker, Peter F. -- (Peter Ferdinand), -- 1909-2005 -- Influence.; Drucker, Peter F. -- (Peter Ferdinand), -- 1909-2005; Industrial management -- Social aspects.; Social ecology.; Industrial management -- Philosophy.; elektronické knihy; electronic books